Literature, travel, and colonial writing in the English Renaissance, 1545-1625 - Hadfield, Andrew (Oxford [England] : Clarendon Press ; New York : Oxford University Press, 1998)
What was the purpose of representing foreign lands for writers in the English Renaissance? This innovative and wide-ranging study argues that writers often used their works as vehicles to reflect on the state of contemporary English politics, particularly their own lack of representation in public institutions. Hadfield explores in his work representations of Europe, the Americas, Africa, and the Far East, selecting pertinent examples rather than attempting to embrace a total coverage. He also offers fresh readings of Shakespeare, Marlowe, More, Lyly, Hakluyt, Harriot, Nashe, and others
Introduction: Changing Places in English Renaissance Literature -- 1. 'How harmful be the errors of princes': English Travellers in (Western) Europe, 1545-1620 -- 2. 'What is the matter with yowe Christen men?': English Colonial Literature, 1555-1625 -- 3. 'The perfect glass of state': English Fiction from William Baldwin to John Barclay, 1553-1625 -- 4. 'All my travels' history': Reading the Locations of Renaissance Plays
Includes bibliographical references (pages 267-296) and index
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism; Travel in literature; British -- Foreign countries -- History -- 16th century; British -- Foreign countries -- History -- 17th century; Travelers' writings, English -- History and criticism; Politics and literature -- Great Britain -- History -- 16th century; Politics and literature -- Great Britain -- History -- 17th century; Imperialism in literature; Travel writing -- History; Colonies in literature; Renaissance -- England